Emerging and evolving values in the changing landscape of genomics - Siermann, Maria; Mohan, Riya; Bunnik, Eline M.; Cambon-Thomsen, Anne; Chadwick, Ruth; Cornel, Martina C.; van Delden, Johannes J. M.; Joly, Yann; Molnár-Gábor, Fruzsina; Nicolás Jiménez, Maria Pilar; Pinxten, Wim; Rial-Sebbag, Emmanuelle; et al. (Frontiers in Genetics, 2025)
Recent advances in human genomics have transformed the field, leading to increased integration of genomics into mainstream clinical care, broadening the potential of personalized medicine, and expanding data generation and sharing. From the outset, genetics and genomics have given rise to a broad array of ethical concerns, including issues related to discrimination and stigmatization, informed consent, and reporting requirements of secondary findings. Ethics considerations and trends have evolved in parallel with the rapid technological progress in genomics. Like other transformative technologies, genomic innovations are governed by a combination of laws and ethics guidelines to ensure their responsible implementation. In this manuscript, we propose three key values that are crucial and timely to address now: equity, collective responsibility in the mainstreaming of genomics, and, sustainability. Equity warrants renewed attention due to its critical role in ensuring fair access to genomic innovations and promoting equality within society at large. Collective responsibility in the mainstreaming of genomics is equally important, especially as genomics becomes more broadly available in healthcare and to the broader public, thereby emphasizing shared accountability in its ethical application. Finally, in a context of scarcity of financial, personnel and environmental resources, sustainability needs to be considered to ensure the future of responsible governance in research and healthcare. The goal is to ensure equal access to genomic innovations, promote the ethically responsible use of genomic technologies, and support the long-term sustainability of the field.